Teaching Strategies of English Teacher with Tour Guide Experiences: A Case Study in Sembalun High Schools - Agina, Meri; Amin, Muhammad; Apgrianto, Kurniawan (Journal of English Education Forum (JEEF), 2024)
This study intended to describe the strategies of English teachers with tour guide experiences used in teaching English and the effects of teachers’ experiences as a tour guide on their teaching. The research used a qualitative research method which implemented a case study approach. The procedures of data collection were observation and interview. Technique of data analysis were data condensation, data display, and verification and conclusion. The result of the data showed that there were 8 (eight) cognitive strategies and 3 (three) metacognitive strategies that teachers used in their teaching. The cognitive strategies include repetition, resourcing, translation, note-taking, elaboration, imagery, and inferencing whereas, whilst, the metacognitive strategies encompass setting learning objectives, creating study plans, and monitoring comprehension and production. Moreover, the effects of English teachers’ experiences as tour guides on their teaching include the teachers' concerns to help students be familiar with several accents and help them understand variations in pronunciation and intonation, then minimizing confusion when students are faced with various accents. Another effect is the process of running the class in which the teachers occasionally involve tourists in classroom activities. Because of this, students can speak directly with them, and improve their English speaking, listening, and understanding skills with authentic accents.